Application of Lean Manufacturing Methods in the Production of Ultrasonic Sensor - Michal Bucko; Vladimira Schindlerova; Hana Krupova (Tehnički Vjesnik, 2022)
The paper deals with the use of lean manufacturing methods for ultrasonic sensors production optimization. The company where this case study was applied is part of a group that is one of the most important suppliers in the automotive industry. It is necessary for companies to constantly improve and innovate their production environment to remain competitive in the market. The current car manufacturers' demands include the pressure to increase production efficiency which can be achieved by implementing lean management. Production processes are never perfect and need to be improved and optimized to achieve the ideal state. The optimization focuses on the part of the sensor production line where the cap and seal are fitted. The ultrasonic sensor is used for measuring the oil level and temperature in a narrow area. The case study aims to optimize the fitting process problem and the resulting product of this process because it does not meet the quality requirements.